The Australopithecines – An Extinct Group of Human Ancestors: My Scientific Interest in South Africa - Kaszycka, Katarzyna A. (Werkwinkel, 2017)
I introduce the subject of my research interest in South Africa - the australopithecines - a group of bipedal, small-brained and large-toothed creatures from the Plio-Pleistocene, from which the human genus arose. I then briefly discuss various topics of my research, concerning: (1) Taxonomic status and morphological description of the extinct human relative from the Kromdraai site (Australopithecus robustus); (2) Graphic reconstruction of the partial skull from Kromdraai – specimen numbered TM 1517; (3) Assessment of size sexual dimorphism of the South African australopithecines (Australopithecus robustus and Australopithecus africanus), which, in terms of facial features, was pronounced – being almost gorilla-sized; (4) Social behavior of a fossil hominid species from around 2 million years ago, which, in terms of the social structure, was most likely a multimale-multifemale one; and (5) An event from the history of paleoanthropology, concerning the content of the 1924/25 photographs of the Taung Child (Australopithecus africanus) - the first australopithecine skull discovered.